Cortisol secretion and rate of bone loss in a population-based cohort of elderly men and women. - Reynolds, R; Dennison, E; Walker, B; Syddall, H; Wood, P; Andrew, R; Phillips, D; Cooper, C (2005)
Although excessive glucocorticoids are a well-recognized cause of osteoporosis, little is known about the role of endogenous glucocorticoids in determining skeletal mass. We have performed a detailed study of the hypothalamic-pituitary-adrenal (HPA) axis to explore the relationships between cortisol secretion and adult bone mass in 151 healthy men and 96 healthy women aged 61 to 73 years. At baseline and 4-year follow-up, bone mineral density (BMD) was measured by dual energy X-ray absorptiometry (DXA) at the lumbar spine and proximal femur; a lifestyle questionnaire was completed; and height, weight, and waist and hip circumferences were measured. At follow-up subjects underwent a very low-dose (0.25 mg) dexamethasone suppression test, a low-dose (1 microg) short synacthen test, and a 24-hour urine collection for measurement of cortisol and its metabolites. In men, elevated peak plasma cortisol was associated with accelerated loss of mineral density in the lumbar spine (r = 0.16, P = 0.05). This relationship remained significant after adjustment for testosterone, estradiol, 25-hydroxyvitamin D, and parathyroid hormone levels (r = 0.22, P = 0.01) and after additional adjustment for age, (BM), activity, cigarette and alcohol consumption, and Kellgren/Lawrence score (r = 0.19, P = 0.03). In contrast in women, elevated peak plasma cortisol was associated with lower baseline BMD at the femoral neck (r = -0.23, P = 0.03) and greater femoral neck loss rate (r = 0.24, P = 0.02). There was no association between plasma cortisol concentrations after dexamethasone or urinary total cortisol metabolite excretion and bone density or bone loss rate at any site. These data provide evidence that circulating endogenous glucocorticoids influence the rate of involutional bone loss in healthy individuals.